JUAN ANTONIO CORTÉS - Lecciones de equilibrio - Damián Sanz, Miguel Ángel (ZARCH, 2013)
JUAN ANTONIO CORTÉSLecciones de equilibrioBarcelona: Fundación Caja de Arquitectos, 2006, 199 págs. Idioma: español